Assessment of antibiotics sensitivity of microbial isolates from fish hatcheries - Durojaiye, Abiola; Olajuigbe, O O; Oramadike, C E; Ogunsanya, A K (Universitas Malikussaleh, 2023)
The study assessed the antibiotics sensitivity of bacterial isolates from fish hatcheries. The result revealed that bacteria of public health importance were isolated, however, the TVC did not exceed 105 CFU/g. A total of 16 isolates were detected. Thirteen (13) antibiotics recorded over 50% resistance, with the highest resistance (100%) observed in amoxicillin clavulanate (AUG). Ofloxime (OFX), gentamycin(GN) and levofloxacin (LBC) recorded the lowest resistance of 18.75%, 37.5% and 43.75% respectively. Only these antibiotics with least recorded resistance had susceptibility ranging between 50% (LBC) and 68.75% (OFX). The overall average resistance of the isolates to antibiotics was 68.75%; susceptibility 26.67% and intermediate 4.58%. Isolates 15 showed the highest resistance of 100%, followed by isolates 12 and 10 with 93.33% and 93.33% resistance, respectively. Resistance range of 60% to 86.67% was observed in isolates 2, 4, 5, 6, 7, 9, 13, 14, 16 and 17. Isolates 3, 8 and 11 had resistance below 50% ranging between 26.67% and 46.67%. The highest multiple antibiotic resistance index (MARI) was observed in isolate 15 with MARI of 1. Isolates 10 and 12 had MARI of 0.93. This was followed in descending order by isolates 2 and 9 (0.86), isolate 5 (0.8), isolate 14 (0.73), isolates 6 and 7 (0.67) and isolates 4, 13, 16 and 17 (0.6). The least MARI recorded were observed in isolates 3 and 11 (0.47) and isolate 8 (0.27), respectively. The emergence of antibiotic resistance on fish farms in Ijebu-Ode region calls for public health intervention strategies.Keywords: antibiotic; fish health; isolates; resistance.